Engineered proteins as multifunctional materials. (December 2020) - Gupta, Maneesh K.; Wagner, Drew T.; Jewett, Michael C.
Abstract: Abstract : Living organisms have engineered remarkable protein-based materials through billions of years of evolution. These multifunctional materials have unparalleled mechanical, optical, and electronic properties and have served as inspiration for scientists to study and mimic these natural protein materials. New tools from synthetic biology are poised to revolutionize the ability to rapidly engineer and produce proteins for material applications. Specifically, advancements in new production hosts and cell-free systems are enabling researchers to overcome the significant challenges of cloning and expressing large nonnative proteins. The articles in this issue cover the mechanical and rheological properties of structural protein materials and nanocomposites; advancements in the synthesis and assembly of optical, electronic, and nanoscale protein materials; and recent development in the processing of protein materials using liquid–liquid phase separation and three-dimensional printing.